The α1 subunit of the GABA(A) receptor modulates fear learning and plasticity in the lateral amygdala - Wiltgen, Brian J.; Godsil, Bill; Peng, Zechun; Saab, Faysal; June, Harry; Van Linn, Michael L.; Cook, James M.; Houser, Carolyn; O’dell, Thomas; Homanics, Gregg E.; Fanselow, Michael (Frontiers in Behavioral Neuroscience, 2009)
Synaptic plasticity in the amydgala is essential for emotional learning. Fear conditioning, for example, depends on changes in excitatory transmission that occur following NMDA receptor activation and AMPA receptor modification in this region. The role of these and other glutamatergic mechanisms have been studied extensively in this circuit while relatively little is known about the contribution of inhibitory transmission. The current experiments addressed this issue by examining the role of the GABA(A) receptor subunit α1 in fear learning and plasticity. We first confirmed previous findings that the α1 subunit is highly expressed in the lateral nucleus of the amygdala. Consistent with this observation, genetic deletion of this subunit selectively enhanced plasticity in the lateral amygdala and increased auditory fear conditioning. Mice with selective deletion of α1 in excitatory cells did not exhibit enhanced learning. Finally, infusion of a α1 receptor antagonist into the lateral amygdala selectively impaired auditory fear learning. Together, these results suggest that inhibitory transmission mediated by α1-containing GABA(A) receptors plays a critical role in amygdala plasticity and fear learning.